GPCR expression in tissues and cells: Are the optimal receptors being used as drug targets? - Insel, PA (Blackwell Publishing Ltd, 2012)
G-protein-coupled receptors [GPCRs, also known as 7-transmembrane (7-TM) receptors] comprise the largest family of membrane receptors in humans and other species and, in addition, represent the greatest number of current drug targets. In this article, we review methods to define GPCR expression and data indicating that individual cells express >100 different GPCRs. Results from studies that have quantified expression of these receptors lead us to conclude that the optimal GPCRs may not be currently used as therapeutic targets. We propose that studies of GPCR expression in individual cells will likely reveal new insights regarding cellular physiology and therapeutic approaches. Findings that define and characterize the most highly expressed GPCRs thus have important potential in terms of identifying new drug targets and novel therapies directed at a wide range of clinical disorders. LINKED ARTICLES: This article is part of a themed section on the Molecular Pharmacology of G Protein-Coupled Receptors (GPCRs). To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2012.165.issue-6. To view the 2010 themed section on the same topic visit http://onlinelibrary.wiley.com/doi/10.1111/bph.2010.159.issue-5/issuetoc